Finite Volume Analysis Of Transient Free Convection Flow Over Vertical Plate (Cfd Simulation) - Hassan Osman Abdalla, Hassan Osman (Universiti Teknologi Petronas, 2011)
ANSYS FLEUNT is used to study the heat transfer response of an incompressible, laminar, transient free convection flow over a semi-infinite vertical plate. Solving model is based on finite volume method (FVM) which is used to solve the non-dimensional governing equations. Obtained results for the details of the velocity and temperature contours and profiles have been presented. This simulation saves a lot of time through designing a simulated model with results similar to the obtained numerical solution. It can give a pre-capturing of the design attributes and characteristics.